La construcción de la identidad de género y su influencia en el resquebrajamiento de los paradigmas tradicionales de la sexualidad de los y las adolescentes que participan en las fiestas semáforo en la institución educativa virgen del carmen del centro poblado alto trujillo - Lozano Mejía, María Ernestina (2014)
Among adolescents from around the world has become fashionable parties called Semaphore, sexual roulette. The first emerges as a very famous imitation among teens movie called "Project X" where the sexual debauchery and alcohol are the main source of fun. The second is a new sexual game played between adolescents, originated in the city of Medellin in Colombia, causing controversy in society. These new forms of entertainment have received in a sector of the adolescents in our country; social networks - such as Facebook - and the media facilitated the promotion and dissemination of these practices. In Peru, the first records of the stoplight partying and sexual roulette game are located in Lima, then these practices are imitated in other provinces. The newspapers can be read headlines like "Rampage sex, drugs and alcohol threat to adolescents" In light parties adolescents manifest Cultural behaviors and socially "inappropriate" that invite the debauchery and excess, resulting in a breakdown in the traditional paradigms of sexuality, manifesting in sexual games, such as "sexual roulette'Í where teenagers usually offer their bodies while teens are in competition to preve their virility and sexual potency. During the investigation 20 in-depth interviews, group sessions and five anonymous 1 encuesta was performed. Knowing how adolescents construct their gender identity, from the approval and prohibition of certain behaviors that are considered strictly male or female. And since this will influence the expression of their sexuality, making or participating in these new teen practices.